MEMBANGUN PC CLONNING BERBASIS WINCONNECT - Utomo, Imam Budi; Maslan, Andi (Computer Science and Industrial Engineering, 2021)
Operating systems have become a necessity today in various government agencies, industry, and universities and have used computers to help with daily work. As users, of course, they want the ease of operating a system, such as sharing files, sharing windows, sharing the internet, and sharing various kinds of multimedia. In connection with sharing an operating system or windows, of course the term remote desktop is known, this term is rarely known by users, even never used. Based on these problems, this study discusses Building a PC Clonning Network Using Winconnect and Remote Desktop. From this problem, the purpose of this research is to build a PC Clonning network that functions to minimize or cover the shortcomings of PC specifications that do not meet the standards accurately, effectively, and efficiently and also to be able to determine the success of the PC Cloning that it has built, so that it can walk more significantly and can be enjoyed. To achieve this goal, direct observation (observation) and descriptive statistics are used, so that the results of these methods have been obtained from observations and statistical analysis in the observation process, with PC Clonning users can access the windows display remotely, save upgrade costs, increase pc performance. The test results in this study showed the success rate of PC Clonning with remote desktop on PC 1 (one) to PC 4 (four), it was seen that before cloning the processor was 0%, memory was 19%, network was 0%, while after the cloning process the processor was still steady at 0%, memory increased to 20% and networking to 0.01%. Second, processor 0%, memory 21%, network 0%, processor 1%, memory 23% and networking to 0.04%. Third, 1% processor, 30% memory, 0% network, 4% processor, memory increased to 32% and networking to 8%. And fourth, processor 7%, memory 63%, network 0%, processor 20%, memory increased to 65% and networking to 0.01%.